Analisis Higher Order Thinking Skills (HOTS) dalam soal-soal matematika semester 1 kelas v sekolah dasar - Novitasari, Evi; Riyadi, Riyadi; Sriyanto, Muhammad Ismail (Universitas Sebelas Maret, 2022)
This research aims to describe the compatibility between the first semester of fifth grade math problems at SD Negeri 3 Tambakmulyo for the 2021/2022 academic year with the integration of Higher Order Thinking Skills (HOTS). The questions are grouped based on the characteristics of HOTS and cognitive level. The research is a qualitative descriptive study with the type of document analysis research. The document being analyzed is a document on math questions for class V semester 1 of the 2021/2022 academic year in the form of practice questions and daily test questions. The result showed that the fifth grade math questions had not yet integrated HOTS. This is because the characteristics of HOTS in math problems are only found in certain basic competencies and the operational verbs used are not HOTS because the number of cognitive C2 (understanding) and C3 (applying) the dominant one. Cognitive level of math problems includes cognitive level C2 (understanding) as many as 48 items or 35,03%, C3 (applying) as many as 84 items or 61,31%, C4 (analyses) as many as 4 items or 2,93% and C5 (evaluative) as many as 1 item or 0,73%.